Radiographic shoulder parameters and their relationship to outcomes following rotator cuff repair: a systematic review. (August 2021) - Zaid, Musa B; Young, Nathan M; Pedoia, Valentina; Feeley, Brian T; Ma, C Benjamin; Lansdown, Drew A
Background: Anatomic parameters, such as the critical shoulder angle and acromion index, have emerged as methods to quantify scapular anatomy and may contribute to rotator cuff pathology. The purpose of this paper is to investigate the published literature on influences of scapular morphology on the development of re-tears and patient-reported outcomes following rotator cuff repair. Methods: A systematic review of the Embase and PubMed databases was performed to identify published studies on the potential influence of scapular bony morphology and re-tear rates and patient-reported outcomes after rotator cuff repair. Studies were reviewed by two authors. Results: A total of 615 unique titles and 49 potentially relevant abstracts were reviewed, with eight published manuscripts identified for inclusion. Two of three papers reported no relationship between these acromion index and rotator cuff re-tear rate, while one paper found an increased re-tear rate. All three studies on critical shoulder angle found a significant association between critical shoulder angle and cuff re-tear rate. There was no clear relationship between any bony morphologic measurement and patient-reported outcomes after rotator cuff repair. Conclusions: Rotator cuff re-tear rate appears to be significantly associated with the critical shoulder angle and glenoid inclination, while not clearly associated with acromial morphologic measurements.